2017
DOI: 10.3389/fchem.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies on Optoelectronic and Nonlinear Properties of Octaphyrin Derivatives

Abstract: The electronic and nonlinear optical (NLO) properties of octaphyrin derivatives were studied by employing the DFT/TDFT at CAM-B3LYP/6-311++G (2d, 2p) level of the theory. Thiophene, phenyl, methyl and cyano moieties were substituted on the molecular framework of octaphyrin core, in order to observe the change in optoelectronic and nonlinear response of these systems. The frontier molecular orbital studies and values of electron affinity reveals that the studied compounds are stable against the oxygen and moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…For this purpose, it has been well-established in the literature that the computational theoryaided design can be a useful tool to optimize the molecular electro-optic performance. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Recently, several works [45][46][47][48][49][50][51][52][53][54][55] have evaluated the NLOP of Hückel and Möbius topologies. For instance, the present authors studied the electronic and vibrational contributions to static and dynamic NLOP of the Hückel-Möbius switch of the bianthraquinodimethane modified [16] annulene 56,57 and A,D-di-p-benzi [28]hexaphyrin(1.1.1.1.1.1).…”
Section: ) Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, it has been well-established in the literature that the computational theoryaided design can be a useful tool to optimize the molecular electro-optic performance. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Recently, several works [45][46][47][48][49][50][51][52][53][54][55] have evaluated the NLOP of Hückel and Möbius topologies. For instance, the present authors studied the electronic and vibrational contributions to static and dynamic NLOP of the Hückel-Möbius switch of the bianthraquinodimethane modified [16] annulene 56,57 and A,D-di-p-benzi [28]hexaphyrin(1.1.1.1.1.1).…”
Section: ) Introductionmentioning
confidence: 99%
“…triangular-shape β e < eight-shape β e < Möbius-shape β e ). And very recently, Islam and Lone 55 computed the electronic NLOP of five octaphyrin derivatives (different meso-susbstituents were considered) with a twisted double-side Hückel topology at CAM-B3LYP level. They concluded that the incorporation of electron-donating groups on the octaphyrin skeleton increases their NLOP.…”
Section: ) Introductionmentioning
confidence: 99%
“…In the present study therefore, we focus attention on the calculation of the internal reorganization energy from first principle. The reorganization energies for the hole and electron transfers have consequently been evaluated at the RIJCOSX-PBE0-D3/ma-def2-TZVP (for the metal ion) and ma-def2-SVP (for the other elements)// B97-3c levels of theory in gas phase using the following formulas in Equation ( 6) and ( 7) [12] [41] and reported in Table 3.…”
Section: Oled Propertiesmentioning
confidence: 99%
“…These materials exhibit properties such as two/multi-photon absorption [3,4], nonlinear scattering [5,6], reverse saturation absorption [7,8], etc. One of the ways to improve the NLO ability of a known compound is to derivatize it, especially by adding an electron donor at one end and an electron acceptor at the opposite end, this enhances asymmetric charge distribution [9][10][11]. Asymmetric charge distribution can be investigated by calculating the tensor components via quantum mechanical calculations [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the molecular first hyperpolarizability is used as a measure of the second harmonic efficiency of a molecule [12]. Density functional theory (DFT) methods have been employed while probing into molecular properties, it has been used in past and in recent times in different areas of materials science research [11,12,[15][16][17][18][19][20][21]. In this study, 4-Methylphenyl) (4-methylpiperidin-1-yl) methanone, (MPMPM; Fig.…”
Section: Introductionmentioning
confidence: 99%